Effect of Expectations on Treatment Outcome for Lumbar Intervertebral Disc Herniation. Issue 9 (May 2016) - Lurie, Jon D.; Henderson, Eric R.; McDonough, Christine M.; Berven, Sigurd H.; Scherer, Emily A.; Tosteson, Tor D.; Tosteson, Anna N. A.; Hu, Serena S.; Weinstein, James N.
Abstract : Study Design: Secondary analysis of randomized and nonrandomized prospective cohorts. Objective: To examine the effect of patient treatment expectations on treatment outcomes for patients with intervertebral disc herniation. Summary of Background Data: Patient expectations about treatment effectiveness may have important relationships with clinical outcomes. Methods: Subgroup and reanalysis of the Spine Patient Outcomes Research Trial, a randomized trial and comprehensive cohort study enrolling patients between March 2000 and November 2004 from 13 multidisciplinary spine clinics in 11 US states. Overall, 501 randomized and 744 observational patients (1244 total) who were surgical candidates with radiculopathy and imaging confirmed lumbar intervertebral disc herniation were enrolled. The primary study compared surgical discectomy to usual nonoperative care; this subgroup analysis reassessed outcomes on the basis of treatment expectations at baseline. Expectations about symptomatic and functional improvement for both surgery and nonoperative care were assessed on 5-point scales (1="No Chance (0%)" to 5="Certain (100%)"). Outcomes were assessed using longitudinal regression models analyzed by treatment received. Results: Among 1244 IDH SPORT participants, 1168 provided data on both outcomes and baseline expectations and were included in the current analysis: 467 from the randomized and 701 from the observational cohort. Low expectations of outcomes with surgery predicted poorer outcome regardless of treatment. High expectations of outcomes with nonoperative care predicted better nonoperative outcomes but did not affect surgical results. These differences were of similar magnitude to the difference in outcomes between surgery and nonoperative care. Conclusion: High expectations of treatment benefit had clinically significant positive associations with outcomes. Level of Evidence: 2